Social and familial maladjustment : social representations in closed educational center for teenagers and youth - KLIKPO, Tchédié Etdéchié Elvyre (My University, 2019)
Social and familial maladjustment is the inability to conform to a group's habits and norms and to participate in its activities and productions. The purpose of this study is to study the social representations of the social and familial maladjustment of adolescents and young people. This is a case study, using a mixed method essentially qualitative, set in a closed educational center in the Department of Littoral in Benin. The study concerned adolescents and young people admitted to the center and their referents. The respondents in the target population were all male and aged 10 to 23 with an average age of 18 years. The social representations of maladjustment, according to young people and their referents are similar. They concern social disqualification, inadequate educational attitudes, the absence of familial model, educational failure linked to adolescents or young people and mystical-religious representations. Adolescents and young people define themselves as deviants while their referents define them as delinquents. This create an insecurity feeling and a need to protect society. Adults have to integrate themselves earlier in the prevention of this phenomenon with the help and /or child psychiatrist lead.
Keywords: Social and Familial Maladjustment; Social Representations; Adolescents; Youth; Referents; Closed Educational Center